From the Liberation of Women to the Liberation of Men? A Century of Family Law Reform in Egypt - Sonneveld, Nadia (Religion & gender, 2017)
To what extent have notions of manhood and womanhood as incorporated in Egyptian Muslim family law changed over the course of almost a century of family law reforms, and why? In answering this question, I draw on the works of two Egyptian intellectuals, Qasim Amin and Azza Heikal, because they discussed ideas about manhood and womanhood in relation to Islamic religion and authoritarian rule. My analysis shows that there is a dire need within studies on gender in the Middle East to assess the effectiveness of family law reform on both women’s and men’s agency. After all, when an authoritarian government introduces legislation that enhances women’s legal rights with regard to the family but does not reform men’s legal rights inside that same family, it is not surprising that when political oppression ends, disenfranchised men will try to abolish the laws that expanded their wives’ freedom and curtailed theirs.